Bactericidal activity of Lys49 and Asp49 myotoxic phospholipases A2 from Bothrops asper snake venom - Páramo Aguilera, Leandro Alberto (1998)
Mammalian group-II phospholipases A2 (PLA2) of inflammatory fluids display bactericidal properties, which are dependent on their enzymatic activity. This study shows that myotoxins II (Lys49) and III (Asp49), two group-II PLA2 isoforms from the venom of Bothrops asper, are lethal to a broad spectrum of bacteria. Since the catalytically inactive Lys49 myotoxin II isoform has similar bactericidal effects to its catalytically active Asp49 counterpart, a bactericidal mechanism that is independent of an intrinsic PLA2 activity is demonstrated. Moreover, a synthetic 13-residue peptide of myotoxin II, comprising residues 1152129 (common numbering system) near the C-terminal loop, reproduced the bactericidal effect of the intact protein. Following exposure to the peptide or the protein, accelerated uptake of the hydrophobic probe N-phenyl-N-naphthylamine was observed in susceptible but not in resistant bacteria, indicating that the lethal effect was initiated on the bacterial membrane. The outer membrane, isolated lipopolysaccharide (LPS), and lipid A of susceptible bacteria showed higher binding to the myotoxin II- (1152129)-peptide than the corresponding moieties of resistant strains. Bacterial LPS chimeras indicated that LPS is a relevant target for myotoxin II-(1152129)-peptide. When heterologous LPS of the resistant strain was present in the context of susceptible bacteria, the chimera became resistant, and vice versa. Myotoxin II represents a group-II PLA2 with a direct bactericidal effect that is independent of an intrinsic enzymatic activity, but adscribed to the presence of a short cluster of basic/hydrophobic amino acids near its C-terminal loop.